Registro sedimentario de la transgresión pliocena al sur de la Sierra Bermeja. (Cordillera Bética, Mediterráneo occidental) - Guerra Merchán, A. (Cuadernos de Geología Ibérica, 1997)
lo tite Pliocene materials locailizated to tite South of Sierra Bermeja (Estepona, Málaga), three lititologie units are differentiated in cartography. Tite lower unit is formed by red conglomerates and sands, and it represents tite alluviál fan deposits. Tite middler unit is originated in marine environments. It is made up by a beacit facies-unit, comprinsing gravels and sands, a shelf facies-unit consisting of sitales witit bentitonie and planktonic fauna and a lan delta facies-unit, comprinsing conglomerates and sands. The upper unit is dominated by borrowed fine sands and sitales deposited in the transition zone. Two retrograding sedimentary cycles are recognized. Tite first is constituted by alluvial, beacl-i and shelf deposits. Tite second is composed of tite fan delta and transition zone deposits. Both cycles were developed in a transgressive context during tite Pliocene, while tite tectonic activity controlled tite subsidence and tite sediment supply. `l’he biostratigraphic data indicate a Lower Pliocene age br titis materials, wbicb can be correlated with Pliocene 1 unit in tite Cordillera Betie area.